2009
DOI: 10.1590/s1516-35982009001100020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding regime and finishing system on lamb muscle fiber and meat quality

Abstract: -The study verified the influence of different nutritional levels of the dams, before parturition, the weaning age of the lambs and the finishing system on lamb muscle fiber morphology and meat quality. Ile-de-France × Bergamacia crossbred dams grazing on natural grassland were divided into two groups: 1) nutritional supplement 30 days before the parturition (SUPL), and 2) no nutritional supplement (NS). These groups were further subdivided by weaning age of the lambs, which corresponded to either 45 or 60 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…The pH was high in winter and autumn and low in summer and spring. These results were also reported by Gallo et al (2009) in light lambs and could be due to high glycogen levels in muscles which is influenced by the fat-content of the feeding regime. The L* values for meat purchased in winter were the lowest, showing a dark colour.…”
Section: Resultssupporting
confidence: 83%
“…The pH was high in winter and autumn and low in summer and spring. These results were also reported by Gallo et al (2009) in light lambs and could be due to high glycogen levels in muscles which is influenced by the fat-content of the feeding regime. The L* values for meat purchased in winter were the lowest, showing a dark colour.…”
Section: Resultssupporting
confidence: 83%
“…In sheep, the proportion of red, intermediate and white fibers is approximately 15, 31 and 54%, respectively (Gerrard and Grant, 2006). For the same species, Gallo et al (2009) reported frequencies of 9.77, 35.01, and 55.21% for red, intermediate and white fibers, respectively. The proportions of these fibers vary between muscles and alter physical-chemical characteristics such as color (Tschirhart-Hoelscher et al, 2006).…”
Section: Muscle Fibersmentioning
confidence: 90%
“…However, Gallo et al (2009) call attention to the fact that composition values can vary according to the animal's condition, resulting in lower protein and water percentage, and high degree of fat. Diaz et al (2002) reported that the humidity of sheep meat varies between 61.32% and 69.08%, which corresponds to a variation between 38.68% and 30.92% in the dry matter.…”
Section: Introductionmentioning
confidence: 99%